Istikhdāmu Wasīlatu Bāzl ‘Alā Tarqiyyati Mahārati Al Kitābati Li Aṭ Ṭullābi Al Fasl Aṡ Ṡāmin Fī Al Madrasah Aṡ Ṡanāwiyyah Al Hukūmiyyah Yaftif Ayyā Gadang Basāmān Garbiyyah - Yulianti, Welly; Arsya, Fajriyani; Dewi, Yelfi; Rizal, Eka (DAS Institute, 2022)
An effort to improve students' educational success is choosing the right teaching medium and getting students' attention. The method used in this study is puzzle, which is a method that teachers can develop using simple materials and tools to help students understand the learning material. The purpose of this study is to know the use of the puzzle method in learning Arabic to improve writing ability. Accordingly, the researcher conducted this study entitled